PENGAKUAN PENDAPATAN DAN BIAYA BERDASARKAN STANDAR AKUNTANSI KEUANGAN PADA RUMAH SAKIT UMUM PUSAT WAHIDIN SUDIROHUSODO DI MAKASSAR - Mufti, Digor (KEUNIS, 2021)
The purpose of this research is to acknowledge the income recognition and the cost of Wahidin Sudirohusodo Centre General Hospital, Makassar. This research applied qualitative data and comparative analysis methods by counting the data recorded in the financial statement and activity report. It is found that the recognition of income and costs has met the PSAK Number 23 where it means it also has satisfied the financial accounting standard”™s guidance. Financial report has qualified opinion dated on December 31, 2017 along with financial performance and cash flow.